Layanan Mobile Ho-Jak, Go-Jek dan Grab Terhadap Perbandingan Pengalaman Pengguna (Studi Pada Konsumen PT. Ho-Jak Indonesia, PT. Aplikasi Anak Bangsa dan PT. Grab Indonesia di Kota Banda Aceh) - Irma Farnita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2017)
This study tested the comparison of user experience (user Experience) on the mobile apps Ho-Jak, Go-Jek and Grab by doing surveys for mecari difference experience felt by a third user group application. User Experience is measured through Variable Sub Happiness, Task Success, Earning and Uptime. This research uses descriptive comparative analysis method with the quantitative approach. The research examined objects i.e. the user Experience. The analysis of the data used are the paired t-test. Based on the results of the study, a descriptive analysis of the Results showed that of the four sub variable user Experience that is Happiness, Task Success, Earning, and the average Uptime of the positive assessment given to applications Go-Jek as a platform that can be deliver a good experience to its users. This is one of them because of the emergence of Ho-Jak comes first in Banda Aceh if compared with the Grab and Go-Jek, thus allowing the Ho-Jak and similar business can better understand the desires of users based on doing the research activities , planning, development and testing that has been done in the neighborhood of Banda Aceh.